Outcomes Of Vipreetmala Taila & Ganesh Kriya In The Treatment Of Anal Stenosis: One Centre Experience - Gupta, Sudesh; Singh, Manpreet (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: An alstenosis represents an abnormal narrowing of the anal canal to a varying extent due to stricture of the epithelial lining that has been replaced by fibrous connective tissue. Although it may occur without previous surgery, it usually results from surgical procedures carried out overzealously without the required technical knowledge, most commonly after hemorrhoidectomy. Sushruta has cited administration of various oils through anus for the treatment of various disorders. The intend of this study was to share the results of oil administration into anus in the management of anal stenosis. Methods: from 2016 to 2018, twelve patients, nine (75%) males & three (25%) females with mild to moderate anal stenosis wereselected from Jammu Institute of Ayurveda & Research, Jammu, India. All the cases were advised for sitz bath followed by Ganesh kriya (Rectum Cleaning/Anal Cleaning) & administration of Vipreetmala taila into anus with red rubber catheter twice a day for one month. Results: All the patients were complaining of Pain (100%) & constipation (100%), nine patients were complaining of Bleeding (75%) & Pain (75%) before treatment. After the completion of third month all the Patients showed complete improvement in all symptoms and follow up of the cases was done for six months. Conclusion: The best remedy for anal stenosis is prevention. Therefore, during common surgical procedures like hemorrhoidectomy, one must refrain from interventions that will result in anal stenosis. However, the ease of administration, good functional outcome, and lack of any complications show that Ganesh kriya (Rectum Cleaning /Anal Cleaning) & administration of Vipreetmala taila into anus is safe, effective &offer commendable results.